Revisiting Lived Experiences of Second-Grade Elementary Teachers on Obstacles to Teaching the Hadiyeh-ha-ye Aseman Textbook - Seyyed Heshmatollah Mortazavizadeh (پژوهش در آموزش معارف و تربیت اسلامی)
Religious education plays a fundamental role in nurturing innate dispositions (fitrah) and fostering religious growth. This study investigates the lived experiences of elementary teachers regarding obstacles in teaching the second-grade Hadiyeh-ha-ye Aseman (Heavenly Gifts) textbook. Using a qualitative approach and descriptive phenomenology, the research focused on elementary teachers in Qom City during the 1403-1404 academic year. A criterion-based purposive sampling method selected 21 teachers, with semi-structured interviews conducted until data saturation (redundancy observed by the 19th interview, but two additional interviews were completed for validation). Inclusion criteria included at least three years of teaching experience in second grade and current teaching at this level. Data analysis followed Strabert and Carpenter’s (2003) method. Peer review and member-checking enhanced validity, while detailed note-taking and meticulous data review ensured reliability. Major obstacles were categorized into four themes: Teacher-related obstacles; Student-related obstacles; Parent-related obstacles; Textbook content-related obstacles, further divided into 21 sub-themes. Recommendations include restructuring the textbook’s chapters, making content more practical, employing active teaching methods, reducing teacher-centeredness, and increasing student participation in learning.